The role of financial literacy in financial inclusion in emerging markets: evidence from South Africa - Kamanga, Tayina (Research of GSB, 2018)
Despite all the efforts and initiatives put in place by governments and development finance institutions to improve financial inclusion, two billion people in the world remain unbanked. The majority of the unbanked population is in the developing countries and mostly in the Sub-Saharan region. This is of huge concern to many governments and their international development partners because it hinders inclusive economic growth. It is argued that consumers can only use products and /or services if they have enough knowledge about these. According to the 2014 World Bank Global Findex database, only 33% of the adults worldwide are financially literate and this average even goes down to 13% in developing countries. It is, therefore, imperative to improve financial literacy of the consumers to increase meaningful participation in the financial sector especially in developing countries. As such it is necessary to understand the relationship between financial literacy and financial inclusion within the Sub–Saharan region. Most of the previous researches in the area of study have been conducted in developed countries and most of them have focused on either the relationship between financial literacy and the demographic factors, or the relationship between financial inclusion and demographic factors. Very few studies have investigated the direct link between financial literacy aspects and financial inclusion indicators. This study accordingly investigates the link between financial literacy and financial inclusion. The study also investigates how socio-demographic and economic characteristics affect financial literacy levels of individuals. Due to the availability of reliable data in South Africa the study uses evidence from South Africa using data collected by the Human Sciences Research Council (HSRC). The main results of the study indicate that use /ownership of financial products is positively and significantly related to financial literacy. The results also indicate that geographical location, age and education attainment have an influence on an individual being financially literate and financially included, but there is no evidence to suggest that living standard measure has an impact on either financial literacy or financial inclusion. The implications of the results of this study are important because they highlight the focus areas for policy makers to achieve optimal results in financial literacy and financial inclusion. In addition, the study adds to the body of knowledge an analysis of a direct link between financial literacy and financial inclusion in an emerging market using widely accepted indicators and a more diverse and nationally representative sample. The study concludes that increasing financial literacy levels would increase the uptake of financial products/services. Based on the results of the study, this research presents conclusions, policy recommendations and recommendations for further research studies that are necessary to improve aspects of financial literacy and financial inclusion.